An integrative taxonomy of Vescelia pieli pieli species complex based on morphology, genes and songs from China (Orthoptera: Grylloidea: Phalangopsidae: Phaloriinae) - Tian, Di; Shen, Chu-Ze; Chen, Lin; Chen, Guang-Yu; Zhang, Tao; Li, Kai; He, Zhu-Qing (Zootaxa, 2019)
There are nine species or subspecies belonging to genus Vescelia Stål, 1877 in the world, with two species distributed in China, V. pieli pieli and V. liangi. During 2018–2019, Vescelia spp. from Hainan, Guangdong and Fujian were systematically investigated. Here, we described two new species, Vescelia dulcis He sp. nov. and V. pieli monotonia He subsp. nov. The new species are similar to V. pieli pieli in morphology except for minute differences in the genitalia. But phylogenetic reconstruction and differences in songs support the validity of the new species. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).